The effect of perceived streakiness on the shot-taking behaviour of basketball players - Csapo, P.; Avugos, S.; Raab, M.; Bar-Eli, M. (European Journal of Sport Science, 2015)
We examine behavioural changes of basketball players arising from the hot-hand belief and use data of 1216 National Basketball Association games to measure the effect of cold and hot streaks on three proxies of shot difficulty. We find that the more consecutive shots players make (miss), the more difficult (easier) shots become along the three dimensions. Furthermore, most players' performance seems to improve during hot streaks because they attempt more difficult shots while no significant decrease in shooting accuracy takes place. This might explain why most previous studies could not find empirical evidence for the hot-hand belief in basketball when considering in-game field goal shooting.